Tissue factor-PAR2 signaling crosstalk in cancer and angiogenesis (Hematology Meeting Reports, 2009)
Tissue factor (TF) has now well recognized roles as a signaling receptor involved in the regulation of angiogenesis, tumor growth, metastasis and inflammation. TF initiates coagulation, leading to thrombin signaling through G protein coupled, protease activated receptors (PAR) 1, 3, and 4.1 However, the signaling activities of the TF-VIIa binary and the TF-VIIa-Xa ternary complex may occur prior to or even independently of generalized coagulation activation that lead to fibrin generation, platelet activation and thrombus formation.2 The TF-VIIa complex activates PAR2 and the product of initiation of coagulation, Xa, while still assembled in the transient ternary TF-VIIa-Xa complex, signals through PAR1 or PAR2.